Rietveld analyses and piezoelectric properties of niobium doped bismuth titanate systems - Aguiar, Éderson Carlos [UNESP]; Simões, Alexandre Zirpoli; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (American Scientific Publishers, 2010)
Bi 4Ti 3- xNbxO 12 (BITNb) samples, with × ranging from 0 to 0.40 were obtained using a polymeric precursor solution. Rietveld analyses confirmed that the powders crystallize in an orthorhombic structure free of secondary phases with space group Fmmm. Raman analysis evidenced a sharp increase in the bands intensity located at 129 cm -1 and 190 cm -1 due the lattice distortion in BIT02Nb and BIT04Nb compositions. UV-vis spectra indicated that addition of niobium causes a reduction of defects in the BIT lattice due the suppression of oxygen vacancies located at BO-6 octahedral. Size and morphology of particles as well as electrical behavior of BIT ceramics were affected by addition of donor dopant. Polarization reversal was investigated by applying dc voltage through a conductive tip during the area scanning and was investigated by piezoresponse force microscopy (PFM). PFM measurements revealed a decrease in piezoelectric response with increasing Nb concentration originating from a reduced polarizability along the a-axis. High spontaneous polarization is noted for the less doped sample due the reduction of strain energy and pin charged defects after niobium addition. Copyright © 2010 American Scientific Publishers.
Keywords: Ceramics; Electrical Conductivity; Morphology; Piezoresponse Force Microscopy; Rietveld Analysis; Scanning Electron Microscopy; Bismuth titanate; Charged defects; DC voltage; Donor dopants; Doped sample; Electrical behaviors; Electrical conductivity; Lattice distortions; Niobium additions; Orthorhombic structures; Piezoelectric property; Piezoelectric response; Piezoresponse force microscopy; Polarizabilities; Polarization reversals; Polymeric precursor solution; Raman analysis; Secondary phasis; Sharp increase; Space Groups; Spontaneous polarizations; UV-vis spectra; Bismuth; Ceramic materials; Defects; Electric conductivity; Piezoelectricity; Polarization; Rietveld analysis; Scanning electron microscopy; Niobium